Social change in India : Crisis and resilience - Singh, Yogendra (New Delhi Har - Anand Publication, 1993)
India is entering a qualitatively new phase of social, economic and cultural development. There is a crisis of paradigms and ideologies about what India seeks to be, or what are its visions of the future. This volume offers an analysis of the changes in the social structure, cultural values and institutions in India, and seeks to assess their implication to the contemporary problems. The author deals with questions such as: Is their a continuity in India$1 (Bs process of social change? What is the relationship between the forces of societal resilience with those of social transformation? What is the shape of the Indian (3z(Bnationalism(3y (Bas a value system today and how are the emerging social and economic force defining the issues of ethnicity, nation-state and civilization. ABOUT THE AUTHOR Professor Yogendra Singh is currently Professor of Sociology at the Centre for the Study of Social Systems, School of Social Sciences, Jawaharlal Nehru University. He has held senior academic positions in the University. He has done fieldwork in several South-Asian countries and lectured at many universities and institutions in Europe, North-America, Japan and South Asia. He has served as Convenor of the National Panel of Sociologists set up by the U.G.C., was associated with the Research Advisory Committees of the ICSSR and the Planning Commission and has been actively engaged in the organisation of the profession of sociology in India and abroad. He is the author of several books and research papers. Some of his publication include Modernization of Indian Tradition; Social Change and Social Stratification; Indian Sociology of Culture; and Essays in Modernization. In recognition of his research contributions, he was conferred the National Nehru Award in Social Sciences of 1991 by the Madhya Pradesh Government.s
Keywords: Social change